2015
DOI: 10.1016/j.scitotenv.2015.07.094
|View full text |Cite
|
Sign up to set email alerts
|

Fighting carbon loss of degraded peatlands by jump-starting ecosystem functioning with ecological restoration

Abstract: Esitetään Jyväskylän yliopiston matemaattis-luonnontieteellisen tiedekunnan suostumuksella julkisesti tarkastettavaksi yliopiston vanhassa juhlasalissa S212 maaliskuun 28. päivänä 2014 kello 12.Academic dissertation to be publicly discussed, by permission of the Faculty of Mathematics and Science of the University of Jyväskylä, in building Seminarium, auditorium S212, on March 28, 2014 at 12 o'clock noon. The wide and rapidly increasing human land use has caused extensive degradation of natural landscapes, ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 119 publications
(128 reference statements)
1
25
0
Order By: Relevance
“…They could proliferate clonally from relict populations and colonize new areas rapidly after the recovery of suitable environmental conditions (see Table ). The fast recovery of the abundances in remnant populations plays an important role in the early recovery of the ecosystem functioning (Kareksela et al., ; Maanavilja, Kangas, Mehtätalo, & Tuittila, ). On the other hand, the rapid recovery of certain competitive species is suspected to hinder the re‐establishment of other species later on (e.g., Hedberg et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…They could proliferate clonally from relict populations and colonize new areas rapidly after the recovery of suitable environmental conditions (see Table ). The fast recovery of the abundances in remnant populations plays an important role in the early recovery of the ecosystem functioning (Kareksela et al., ; Maanavilja, Kangas, Mehtätalo, & Tuittila, ). On the other hand, the rapid recovery of certain competitive species is suspected to hinder the re‐establishment of other species later on (e.g., Hedberg et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…However, one study in Finland found that restoration operations on a previously drained minerotrophic fen achieved 50% cover of peat‐forming species (e.g., Eriophorum vaginatum , which evolves to Carex and Sphagnum ) already in 3 years [ Jauhiainen et al ., ]. Other studies report recovery of peat‐forming Sphagnum mosses within a few years of restoration [ Laine et al ., ; Maanavilja et al ., ], while reestablishment of whole wetland communities may take much longer [ Haapalehto et al ., ; Kareksela et al ., ]. Furthermore, restoration operations performed on peatlands drained for forestry have been shown to result in more rapid recovery than operations on cut‐away peatlands [ Huopalainen et al ., ].…”
Section: Discussionmentioning
confidence: 99%
“…The greatest hydrological change caused by drainage is the decadal drawdown of water table observed in our study. This drawdown affects not only peatland structures, such as above and below ground communities (Laine et al 1995;Jaatinen et al 2007), but also ecosystem functions such as soil respiration, nutrient circulation and accumulation of peat and C (Braekke 1987;Martikainen et al 1995;Mäkiranta et al 2009;Kareksela et al 2014). As the average water table level could be re-established and maintained for 10 years, restoration of studied peatlands was successful in regaining the single most important condition needed for further recovery of ecosystem.…”
Section: Discussionmentioning
confidence: 99%